MEMAHAMI ASPEK PARALINGUISTIK DALAM KEGIATAN PENYULUHAN PERPUSTAKAAN - Winoto, Yunus; Yusup, Pawit M; -, Sukaesih (Universitas Pendidikan Indonesia, 2017)
Communication is an activity that can not be released in everyday human life. So also in the activities of the library, communication activities are suatau activities that are not separated in the activities of everyday librarians. Especially when referring to the core competence of librarians there are at least two communication activities that are often done ielibrary service activities and library promotion. The success of a librarian as a communicator in delivering communication messages on service activities, counseling and technical guidance library, one of which is determined by the aspect of communicator or speaker (resource). One aspect of the communicator in conveying his communication message is the ability of how when delivering messages verbal communication or better known as paralinguistik. Parallelistic ability will be a speaker's attractiveness aspect (source atrrativeness) and this aspect will be the basis for building participants' perceptions of the credibility of a speaker. Therefore, the understanding of the paralinguisitik aspect becomesimportant for a counselor, including in this case the librarian when going to conduct extension activities and tennis guidance about the library.